Comparative phylogeography of the wild‐rice genus Zizania (Poaceae) in eastern Asia and North America1. Issue 2 (1st February 2015) - Xu, Xin‐Wei; Wu, Jin‐Wei; Qi, Mei‐Xia; Lu, Qi‐Xiang; Lee, Peter F.; Lutz, Sue; Ge, Song; Wen, Jun
Abstract : Premise of the study: Comparative phylogeography of intercontinental disjunct taxa allowed us not only to elucidate their diversification and evolution following geographic isolation, but also to understand the effect of climatic and geological histories on the evolutionary processes of closely related species. A phylogeographic analysis was conducted on the eastern Asian‐North American disjunct genus Zizania to compare intracontinental phylogeographic patterns between different continents. Methods: Surveys were conducted of 514 individuals using three chloroplast DNA fragments and three nuclear microsatellite loci. These individuals included 246 from 45 populations of Zizania latifolia in eastern Asia, and the following from North America: 154 individuals from 26 populations of Z. aquatica, 84 individuals from 14 populations of Z. palustris, and 30 individuals from one population of Z. texana . Key results: The genetic diversity of North American Zizania was significantly higher than that of eastern Asian Zizania . High levels of genetic differentiation among populations and no signal of population expansion were detected in three widespread species. No phylogeographic structure was observed in Z. latifolia, and discordant patterns of cpDNA and microsatellite markers were observed in North American Zizania . Conclusions: Reduced variation in Zizania latifolia likely reflects its perennial life history, the North American origin of Zizania, and the relative homogeneity of aquatic environments. High levels of genetic differentiation suggest limited dispersal among populations in all Zizania species. The more complex patterns of diversification and evolution in North American Zizania may be driven by the greater impact of glaciation in North America relative to eastern Asia.